Characteristics of and Prognosis for Facial Palsy in Patients With Otitis Media With ANCA-Associated Vasculitis (OMAAV). Issue 10 (December 2021) - Fujiwara, Keishi; Morita, Shinya; Fukuda, Atsushi; Yanagi, Hiroko; Hoshino, Kimiko; Nakamaru, Yuji; Furuta, Yasushi; Homma, Akihiro
Abstract : Objectives: The aim of the present study was to investigate the characteristics and prognosis of facial palsy in patients with otitis media with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (OMAAV). Study Design: Retrospective case review. Setting: Tertiary referral center. Patients: Thirty-seven patients with OMAAV. Main Outcome Measures: The patients were divided into the facial palsy group and non-palsy group. The severity of and prognosis for facial palsy were evaluated using the House–Brackmann facial grading system (HB). Characteristics were compared between the facial palsy group and non-palsy group. Results: Facial palsy was observed in eight patients. The last HB grade for all patients was either grade I or II after treatment with a combination of corticosteroids and immunosuppressant therapy. There were no cases in which palsy relapsed. Facial palsy in OMAAV was significantly more common in female patients, and patients with facial palsy demonstrated significantly higher rates of hypertrophic pachymeningitis than did those without facial palsy. Conclusions: Facial palsy in patients with OMAAV was detected in 21.6% and a good prognosis was obtained by use of the appropriate treatment. Facial palsy is one of the most important symptoms by which to diagnose OMAAV. When encountering the patients with intractable otitis media complicated with facial palsy, appropriate examination including ANCA titer should be performed.